Application of Snowball Throwing Model in Science Subjects on Student Learning Outcomes at Junior High School - Mawaddah , Hayyatun; M.P Alibasyah, Lestari (Universitas Tadulako, 2023)
This study aimed to describe the effectiveness of the snowball-throwing learning model in improving student learning outcomes in science subjects in junior high school. This quantitative descriptive research uses an experiment method and pretest-posttest one-group design. The research population was all VIII class students of Junior high school, 19 Palu in the 2022 / 2023 school year, totalling 107 people, with a research sample of VIII A class totalling 31 people. The sample was determined using a non-probability sampling technique, a simple random sampling method. The research instrument consisted of an evaluation test and a teaching observation sheet. Data analysis was carried out using non-parametric statistics and the Wilcoxon signed rank test to test the hypothesis of pretest and posttest data. At the same time, the data from the student activeness observation sheet was carried out descriptively per cent. As for determining the effectiveness of the learning carried out, using the N - Gain test. The pretest and posttest data analysis results obtained a significant probability value < α (0.05). Thus, it can be stated that the proposed research hypothesis is accepted, and it can be noted that the snowball-throwing learning model is efficacious in improving student learning outcomes. Gain test results show that the efficacy of snowball throwing learning is high with an N - -gain value of 0.8, with an N score of 80 % in the practical category. This achievement is supported by the observations of student activeness, with a percentage of 81.8 % in the outstanding category. It can be concluded that the snowball-throwing learning model effectively improves student learning outcomes in science subjects at Junior high school 19 Palu.